Fahrassistenz: Historische Perspektiven auf automobile Assistenzsysteme - Zimmer-Merkle, Silke (Karlsruher Studien Technik und Kultur, 2024)
Driving assistance systems are automotive basic equipment whilst promises of autonomous driving are still subject of dispute. Both are based on ideas of simplifying and automating the driving process that have a long history. The interdisciplinary study shows how the early automobiles of the late 19th century became the car we know today by means of assistance systems only. This volume reveals the role they played throughout the history of the automobile.